Magic triumphs ebook - Andrews, Ilona (Kate Daniels, 2018)
Mercenary Kate Daniels must risk all to protect everything she holds dear in this epic, can't-miss entry in the thrilling #1 New York Times bestselling urban-fantasy series. Kate has come a long way from her origins as a loner taking care of paranormal problems in post-Shift Atlanta. She's made friends and enemies. She's found love and started a family with Curran Lennart, the former Beast Lord. But her magic is too strong for the power players of the world to let her be. Kate and her father, Roland, currently have an uneasy truce, but when he starts testing her defenses again, she knows that sooner or later a confrontation is inevitable. The Witch Oracle has begun seeing visions of blood, fire, and human bones. And when a mysterious box is delivered to Kate's doorstep, a threat of war from the ancient enemy who nearly destroyed her family, she knows her time is up. Kate Daniels sees no other choice but to combine forces with the unlikeliest of allies. She knows betrayal is inevitable. She knows she may not survive the coming battle. But she has to try. For her child. For Atlanta. For the world.